In vitro antifungal screening of some medicinal plants against Macrophomina phaseolina - Balamurugan, S; Selvamani, S; Savitha, G (Current Botany, 2012)
The medicinal plants present enormous reservoir of potential microbial compounds that could be useful alternative to synthetic microbicides and are being used to develop drugs. In the present study of five selected medicinal plants the leaf powder extracts were tested against Macrophomina phaseolina by disc diffusion method. It was found that ethanol extract strongly effective against Macrophomina phaseolina, is a causal agent for charcoal rot of sunflower fungal pathogen.